The Effect of Soil Environmental Parameters on Mangrove Tree Growth in Lingga District - Kamaruddin Eddiwan; Andri Hendrizal (Jurnal Penelitian Pendidikan IPA, 2024)
This study was conducted in Lingga District, Lingga Regency with the aim of determining the effect of environmental parameters such as physical and chemical properties of soil on mangrove forest communities in Lingga Regency. The results showed that soil quality affected mangrove growth in two research locations, where the low soil pH was around 6.1-6.8 but still supported the growth of mangrove trees. The two research locations had soil from the dusty clay texture class, found in all sampling locations, and this land was still suitable for mangrove growth, so it did not interfere with mangrove life in the research location.